A comprehensive review of Schisandrin B’s preclinical antitumor activity and mechanistic insights from network pharmacology - Fang, Yanhua; Pan, Juan; Wang, Piao; Wang, Ruoyu; Liang, Shanshan (Frontiers in Pharmacology, 2025)
As an active constituent in the extract of dried fruits of Schisandra chinensis, Schisandrin B exhibits diverse pharmacological effects, including liver protection, anti-inflammatory and anti-oxidant. Numerous studies have demonstrated that Schisandrin B exhibits significant antitumor activity against various malignant tumors in preclinical studies, which is achieved by inhibiting cell proliferation and metastasis and promoting apoptosis. As a potential antitumor agent, Schisandrin B holds broad application prospects. This review systematically elaborates on the antitumor effect of Schisandrin B and the related molecular mechanism, and preliminarily predicts its antitumor targets by network pharmacology, thereby pave the way for further research, development, and clinical application.